Analysis the technical Performance for Iraqi Foot ball team and Comparison With anther Asian teams - Kadhim, Emad (Journal of Physical Education, 2008)
The aim of research is about knows the ability of Iraqi team players in performance the technical duties in foot ball. The researcher hypotheses making many wrongs in technical performance cause negative influence in all team performance. The sample of research consist of Iraqi foot ball team players. The researcher concludes many things and most important of these conclusions is that : The high level of technical performance in the Iraqi football team when comparisoned this level with another assian teams. Then the researcher recommended the coaches must take care by technical states and also take care by static shoots because it the matches of the football.